The role of contingency theory for tourist destinations management - Kaya, Eda; Kaya, Muhammet Caner (Tourist Destination, 2023)
Contingency theory, known for its ability to adapt to dynamic conditions in an environment, has increasingly come to the fore as an agent of change in the ever-changing environment of the tourism industry. This study looks at the application of contingency theory in the tourism industry, with a particular focus on crisis management, community engagement, technological integration and the promotion of sustainable practices. The potential of the theory to be effective in managing uncertainties and promoting resilience in tourism destinations is presented in its ability to provide perspective. Furthermore, the paper recommends the application of the studies presented to investigate the enduring effects of contingency-oriented strategies on the long-term viability of tourism destinations. This paper emphasizes the interaction between contingency theory and new paradigms such as ecotourism, sustainable development and heritage conservation. It also suggests using contingency theory as a framework for understanding visitor behavior to increase the resilience, sustainability, and resilience of tourism destinations that are dynamic and complex.